Molecular functional group and optical analysis on chlorophyll of green choy sum and cassava leaves extracts. Issue 1 (March 2020) - Palupi, Endah Kinarya; Nazopatul, P H; Umam, Rofiqul; Bibin Andriana, B; Sato, Hidetoshi; Alatas, Husin; Irzaman,
Abstract: Recently, chlorophyll can improve the optical characteristics of thin films. The role of chlorophyll is a dopant in the thin film. Chlorophyll is very good in transferring electron which is strongly related to energy. If the energy gap of the film is low, the characteristics of the film are better because it requires less energy to jump one electron from the valence band to the conduction band. However, an important factor to consider in this case is the chlorophyll content. The more chlorophyll content will improve the light absorption rate. This study examined the characterization of chlorophyll of green choy sum and cassava leaves extracts. The analysis was carried out based on the Fourier Transform Infra-Red (FTIR) and UV-Vis Spectrophotometer. The results of the analysis were molecular functional groups, vibration frequencies, bond force constants between molecules, optical characteristics and chlorophyll content on both of chlorophyll extracts.